Oil Absorbent Polypropylene Particles Stimulate Biodegradation of Crude Oil by Microbial Consortia - Vita, Madalina M.; Iturbe-Espinoza, Paul; Bonte, Matthijs; Brandt, Bernd W.; Braster, Martin; Brown, David M.; van Spanning, Rob J. M. (Frontiers in Microbiology, 2022)
Oil absorbent particles made from surface-modified polypropylene can be used to facilitate the removal of oil from the environment. In this study, we investigated to what extent absorbed oil was biodegraded and how this compared to the biodegradation of oil in water. To do so, we incubated two bacterial communities originating from the Niger Delta, an area subject to frequent oil spills, in the presence and absence of polypropylene particles. One community evolved from untreated soil whereas the second evolved from soil pre-exposed to oil. We observed that the polypropylene particles stimulated the growth of biofilms and enriched species from genera Mycobacterium, Sphingomonas and Parvibaculum. Cultures with polypropylene particles degraded more crude oil than those where the oil was present in suspension regardless of whether they were pre-exposed or not. Moreover, the community pre-exposed to crude oil had a different community structure and degraded more oil than the one from untreated soil. We conclude that the biodegradation rate of crude oil was enhanced by the pre-exposure of the bacterial communities to crude oil and by the use of oil-absorbing polypropylene materials. The data show that bacterial communities in the biofilms growing on the particles have an enhanced degradation capacity for oil.